Soybean Imports and Economic Resilience: Measuring Their Impact on National Development - Kusuma, Putri Patria; Dewanta, Awan Setya; Margaret, Silvia; Azalia, Areta Nur Fatimah (Universitas Negeri Semarang, 2025)
Soybeans play an important role in meeting the consumption needs of the Indonesian people. Soybeans also serve as the main raw material in various food industries in Indonesia, such as tofu, tempeh, soy sauce, and other processed products. The high domestic demand has not been matched by domestic production capacity, so Indonesia still relies on imports to meet these needs. This study aims to analyze the factors influencing soybean import volumes in Indonesia using data spanning 23 years, from 2000 to 2022 (time series). This study uses data obtained from official sources such as the Central Statistics Agency (BPS), the Food and Agriculture Organization (FAO), the World Bank, and the Agricultural Information System (AMIS). The method used is a quantitative approach with the Autoregressive Distributed Lag (ARDL) regression technique. This study aims to analyze the influence of GDP, inflation, exchange rate, and production variables on the volume of soybean imports in Indonesia. A series of steps were conducted, starting from stationarity tests, selection of the optimal lag, cointegration tests, to ARDL model estimation. The results show that in the short term, none of the variables have a significant effect. However, in the long term, only GDP and exchange rate have a significant and positive effect on soybean imports.